Implications of Entrepreneurship and Simple Accounting Knowledge of Endek Crafting MSMEs on Economic Improvement and Preservation of Bali Culture - ADYATMA, I Wayan Chandra; NIDA, Desak Rurik Pradnya Paramitha; YOGA, I Gusti Agung Prama (PT Keberlanjutan Strategis Indonesia, 2024)
Riches Indonesian culture is abundant has push development various product in almost all area with varied styles.? One of from inheritance valuable Balinese culture historical, cultural, and economic is cloth endek. However, with changing times and styles modern living, fabric endek start threatened extinct. Study This highlights two problems main in industry endek in Bali: lack of Skills entrepreneurship and knowledge good accounting, as well low ability recording finance. Research methods applied? is qualitative, with focus on the cause decline amount craftsman endek in Klungkung and efforts regeneration through interaction with generation young. Research result show that potency industry endek in Klungkung For increase economy local and preserving Balinese culture is huge, however lack of participation generation young become challenge main. Skills entrepreneurship and knowledge accountancy identified as solution potential for overcome challenge this. Collaboration between government, community local, and craftsmen required for give support, training, and promotion necessary for the industry endek can Keep going develop and become asset important in preservation Balinese culture.